PERSEPSI GURU TERHADAP BUKU TEKS BAHASA INDONESIA KURIKULUM 2013 KELAS VII SMP NEGERI KOTA BENGKULU - Fatemah Dela Agusfina (Universitas Bengkulu, 2018)
The purpose of this study is to determine the perceptions of Indonesian teachers on Indonesian textbooks of the curriculum of 2013 class VII in terms of material or content and presentation aspect. This study uses purposive samples, the sample of this study are 9 Indonesian VII class teachers who already have certification or professional teachers in SMPN 1, 3, 4, 11. and 18 Kota Bengkulu. Data collection techniques used in this research is a questionnaire. Data analysis technique used this research is descriptive technique and simple count presented in tabular form. The result of the research shows that (1) teacher's perception on Indonesian textbooks of grade VII curriculum in material or content aspect get average grade 4,14 with appropriate criteria, (2) teacher perception on Indonesian text book of 2013 curriculum of class VII in The presentation aspect earned an average rating of 4.02 with the corresponding criteria. Keywords: perception, teachers, textbooks